2000
DOI: 10.1182/blood.v96.1.34
|View full text |Cite
|
Sign up to set email alerts
|

Human endothelial cells express CCR2 and respond to MCP-1: direct role of MCP-1 in angiogenesis and tumor progression

Abstract: Although several CXC chemokines have been shown to induce angiogenesis and play roles in tumor growth, to date, no member of the CC chemokine family has been reported to play a direct role in angiogenesis. Here we report that the CC chemokine, monocyte chemotactic protein 1 (MCP-1), induced chemotaxis of human endothelial cells at nanomolar concentrations. This chemotactic response was inhibited by a monoclonal antibody to MCP-1. MCP-1 also induced the formation of blood vessels in vivo as assessed by the chic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
312
1
10

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 738 publications
(336 citation statements)
references
References 38 publications
13
312
1
10
Order By: Relevance
“…Earlier work on endothelia had shown these cells to express CXCR1, 2, 3 and 4 but not b-chemokine receptors [22]. More recently CCR2, 3, 4 and 5 have also been identified [25,27,39]. Our studies agree broadly with the set of receptors identified by other researchers, although CCR2 was very low.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Earlier work on endothelia had shown these cells to express CXCR1, 2, 3 and 4 but not b-chemokine receptors [22]. More recently CCR2, 3, 4 and 5 have also been identified [25,27,39]. Our studies agree broadly with the set of receptors identified by other researchers, although CCR2 was very low.…”
Section: Discussionsupporting
confidence: 91%
“…In vivo, it is more likely that secreted chemokines would be retained at the endothelial surface for some time and would then be released into the bloodstream. The functions of the endothelial chemokine receptors remain open [25,[37][38][39]42]. However, regardless of their function, this study shows that one phenotypic difference between endothelia lies in their profile of chemokine receptors.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, based on several in vitro studies, the current belief is that MCP-1 does not promote proliferation or prosurvival characteristics in mammary tumor cells. (41) Monocyte chemoattractant protein-1 (MCP-1) is known as the most potent chemoattractant involved in macrophage migration. (42) One of the important roles of MCP-1 in tumor progression is through its involvement in macrophage recruitment relating to inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…In response to the cytokines released by the tumor, EPCs are mobilized from bone marrow to the peripheral blood, home into the tumor site, differentiate into mature endothelial cells (ECs), and secrete angiogenic molecules to facilitate tumor vascularization (9,10). Numerous studies have demonstrated that several factors, such as VEGF, ABBREVIATIONS: 2D, 2-dimensional; 3D, 3-dimensional; CINC-2, cytokineinduced neutrophil chemoattractant 2; CM, conditioned medium; CT, computed tomography; EC, endothelial cell; EPC, endothelial progenitor cell; FCS, fetal calf serum; H&E, hematoxylin and eosin; MCP-1, monocyte chemoattractant protein 1; MIP, macrophage inflammatory protein; MMP, matrix metalloproteinase; PDGF, platelet-derived growth factor; PET, positron emission tomography; SP-MAP, shifted Poisson maximum a posteriori; TAM, tumor-associated macrophage; TRAIL, TNF-related apoptosis-inducing ligand macrophage inflammatory protein 2 (MIP-2), monocyte chemoattractant protein 1 (MCP-1), and TNF-related apoptosis-inducing ligand (TRAIL), play a crucial role in functional properties of ECs (10)(11)(12)(13)(14). The angiogenic switch, necessary for initiation of vessel formation, has long been identified to be orchestrated by the activity of angiogenic molecules (15).…”
mentioning
confidence: 99%